Dynamics of professional burnout - a comparative analysis considering the selected sectors in Poland, part II = Dynamika wypalenia zawodowego - analiza porównawcza z uwzględnieniem głównych branż w Polsce, część II - Witkowski, Stanisław; Ślazyk-Sobol, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The article is a continuation of the study presented in the text entitled: "Professional burnout - a comparative analysis considering the selected sectors in Poland". Management. University of Zielona Góra, Faculty of Economics and Management, Vol. 16, No.2., (p. 87 - 102). The authors present the results of the second part of the research on analysing the phenomenon of burnout among employees of the major sectors in Poland. The present material relates to the results of the re-test conducted after the nine-month interval. One again the cause-effect dependency models for the verified variables were presented for all the tested employed people and separately for each of the specified sectors. The most relevant applicable conclusions resulted from the implemented research projected were formulated.
Keywords: wypalenie zawodowe; dynamika wypalenia zawodowego; cynizm; wyczerpanie emocjonalne; obniżone poczucie osiągnięć; klimat organizacyjny; burnout; dynamics of professional burnout; cynicism; emotional exhaustion; reduced sense of achievements; organisational climate